Quantitative Evaluation of Dental Biofilm Accumulation in Elastomeric Ligatures in Relation to the Amount of Time Within the Oral Cavity - Hélida Neiva CAMPOS; Cátia Cardoso Abdo QUINTÃO; Roberto Sotto-Maior Fortes OLIVEIRA; Robert Willer Farinazzo VITRAL (Association of Support to Oral Health Research (APESB), 2006)
Objective: The aim of this study was to evaluate the amount of dental biofilm accumulation in the elastomeric ligatures of orthodontic patients, and compare the volume of biofilm on these ligatures after one, two, three and four weeks of use. Method: Twenty patients with permanent dentition were selected from the Clinic of Orthodontics of the UFJF. No specific instructions regarding oral hygiene were given to these patients. After prophilaxis, only the four second premolars of each patient in the sample received the same type of elastomeric ligatures. All ligatures were individually stored in a Petri plaque, prepared and numbered. Each plaque received one ligature and was weighed in an analytic scale up to two hours before its insertion into the oral cavity. The elastomeric ligatures were removed from the second premolars after one, two, three and four weeks respectively. The ANOVA and the Student's "t" test were applied (P< 0.05). Results: The results showed a weekly and progressive increase in weight of the elastomeric ligatures, being the second week the least relevant. It could be verified that the difference between the initial and final weights was statistically significant. Conclusion: The elastomeric ligatures can accumulate a considerable amount of dental biofilm which tends to increase with time.